1981
DOI: 10.1115/1.3230735
|View full text |Cite
|
Sign up to set email alerts
|

Conventional Probes for the Relative Flow Measurement in a Turbomachinery Rotor Blade Passage

Abstract: This paper reports the measurement of the relative flow in the rotor blade passages of an axial-flow compressor and an axial-flow inducer using conventional probes such as five-hole, disk, and spherical pitot-static probes. The five-hole probe provides an inexpensive, yet accurate, method of deriving the three-dimensional flow field in a rotor; the disc probe is suitable for the blade boundary-layer measurement; and the pitot-static probe is useful for obtaining the static and stagnation pressures and the tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1985
1985
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Recent investigations [25] have shown that the turbulence intensity affects the calibration characteristics of multihole probes and suggested that the multihole probes should be calibrated at the same turbulence intensity of the flow to be measured. Sitaram et al [26] have discussed these and other sources of errors in the application of five-hole probes and they gave estimates of their magnitudes. Near the wall, the flow is modified due to the presence of the probe and the probe gives erroneous results.…”
Section: Comparison Of Measurements In a Calibration Ductmentioning
confidence: 99%
“…Recent investigations [25] have shown that the turbulence intensity affects the calibration characteristics of multihole probes and suggested that the multihole probes should be calibrated at the same turbulence intensity of the flow to be measured. Sitaram et al [26] have discussed these and other sources of errors in the application of five-hole probes and they gave estimates of their magnitudes. Near the wall, the flow is modified due to the presence of the probe and the probe gives erroneous results.…”
Section: Comparison Of Measurements In a Calibration Ductmentioning
confidence: 99%
“…Each of the pressure holes in the probe head was connected to a pressure transducer with high sensitivity. This probe was carefully calibrated in a calibration tunnel, where the pressures measured and the corresponding pitch or yaw angle was related through the relationships proposed by Sitaram et al (1981). The relationships were actually approximated by two-variable 4-th order polynomials whose coefficients were determined by the least square method.…”
Section: Instrumentation and Data Processingmentioning
confidence: 99%
“…The main application of the FHP would be in location where it would be difficult to use a laser, such as the rotating frame of reference in a turbine or in geometrically difficult situations to reach flow zones. Sitaram et al have performed a detailed study on which type of probe to use within the rotating frame of a single stage compressor research rig at the Pennsylvania State University [11]. Town and Camci presented their early observations about using a subminiature Five-Hole Probe in an axial flow turbine rig in [12].…”
Section: Introductionmentioning
confidence: 99%